Innovation and profitability in a population of Italian listed companies in a time of crisis - Bartolacci, Francesca; Paolini, Antonella; Zigiotti, Ermanno (Piccola Impresa / Small Business, 2016)
This work analyzes the relationship between innovation and performance in a population of Italian listed companies, with special reference to the time period before and during the economic-financial crisis. The analysis examines the relationship between the number of patents registered and the trend of performance indicators, such as turnover and return on invested capital (ROI), with 1 and 2-year delay. Although the results do not identify a precise trend for the entire sample, regular behaviors emerge: with the approaching crisis, a high reduction in the average number of patents and a worse performance are recorded. Nevertheless, with reference to these trends, no relationship between the two variables was identified.